Moves and steps analysis of the message from CEO in in-flight magazines - Narudol Semchuchot; Wannana Soontornnaruerangsee (Asian Journal of Media and Communication, 2017)
This study was aimed to investigate English language moves and steps of thirty purposively selected messages from the CEO in in-flight magazines from five airlines (British Midland Airlines, Gulf Air, Jetstar Airways, Thai Airways International and United Airlines) by adopting Bhatia’s (2014) sales promotion letter model. The findings revealed that the three most frequently found moves were considered obligatory basing on Kanoksilapatham’s (2007) proposition. The three moves were Move 7 ‘Ending politely’, Move 1 ‘Establishing Credentials’ and Move 2 ‘Introduction of the offer’, respectively. Moreover, it was also found that the most prominent organization of moves found in the corpus was Move 1 followed by Move 2 and Move 7. Move 2, which comprised three steps, ‘Offering the product or services’, ‘Essential detailing of the offer’ and ‘Indicating value of the offer’, was found to be the most repetitive. The findings of the study could be a guideline for international communication in English, English writing pedagogy as well as business communication.   Keywords: moves and steps analysis; message from CEO; in-flight magazine; international communication